Implementasi Program Kecakapan Hidup Melalui Pelatihan Tata Boga Bagi Warga Belajar Paket C di SPNF SKB 1 Samarinda - Hizkia Romayani Situmorang; Saraka M Ali; Hepy Tri Winarti (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was motivated by the concern of the SPNF SKB 1 Samarinda institution towards increasing the skills and knowledge learing residents. The aims of the research are (1) to describe of the Life Skills program through culinary training for residents studying Package C at SPNF SKB 1 Samarinda, (2) to describe the success factors for implementing the Life Skills program through culinary training for residents studiying Package C at SPNF SKB 1 Samarinda. This research uses a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The informants consisted of 1 head of the institution, 1 instructor, and 2 students. Data analysis techniques use data reduction, data presentation, and drawing conclusions. Validity of data using triangulation of techniques and sources. The research results show that Implementation of the Life Skills Program through Culinary Training has been carried out optimally, through several stages, namely training plainning, analysis of training needs through socialization, joint discussions and data collection tailored to the needs of learning residents, as well as funding allocated compregensively for training through central government. Secone, the training is carried out through practical methods, with the instructors role as informator, facillitator, motivator and evaluator, then the media used is audio and visual and teaching materials with modules created by the instructor. The three evaluations were carried out through observations of the training implementation with question and answer. The success factors in implementation with questions and answers the competence of competent instructors, active participation of learning residents in the training, as well as complete facillities and infrastructure.